Análise dos aspectos presentes na descontinuidade das exportações por parte das PMEs gaúchas - Dahmer, Gerson Gladimir (Universidade do Vale do Rio dos Sinos, 2021)
Exports by small and medium-sized enterprises (SMEs) have been an important alternative for increasing the countries' trade balance, especially those in development. However, it is not uncommon for SMEs to fail to prosper, discontinuing export activity long after it started. Subject to the same conditions as those that thrive on exports, understanding why different results are important to reduce the percentage of SMEs that abandon export activity. Therefore, this dissertation aims to identify and understand the stimulus factors that led SMEs to export and as barriers that contributed to their discontinuity. Research was carried out with 12 exporting SMEs from the state of Rio Grande do Sul, from the most varied segments, who started exporting in the last 24 years, but who did not export in the last 5 years. An interview was also conducted with their managers, responsible for decisions involving the export area. The data collected through the QCA method, a methodology that allows quantitative and qualitative analyzes together. The results as the main factors present in the discontinuity of exports, the “lack of planning for export activity”, the “lack of international guidance from SME managers”, the “lack of knowledge on how to prospect customers and businesses abroad”, “Lack of support from the Federal Government” and the “exchange rate variation”.
Keywords: Descontinuidade das exportações; Internacionalização de PMEs; Exportação de PMEs; Fatores de estímulos às exportações; Barreiras às exportações; Export discontinuity; Internationalization of SMEs; Exports of SMEs; Factors to stimulate exports; Barriers to exports; ACCNPQ::Ciências Sociais Aplicadas::Administração